Updated cost-effectiveness analysis of tislelizumab in combination with chemotherapy for the first-line treatment of advanced gastric cancer or gastroesophageal junction adenocarcinoma - Xu, Lei; Long, Yunchun; Yao, Lu; Wang, Hao; Ge, Weihong (Frontiers in Oncology, 2024)
ObjectiveThe RATIONALE-305 trial demonstrated that tislelizumab in combination with chemotherapy regimens was more beneficial than chemotherapy regimens alone in the treatment of patients with advanced gastric cancer or gastroesophageal junction adenocarcinoma (GC/GEJC). This study aimed to evaluate the cost-effectiveness of tislelizumab combination chemotherapy in the treatment of advanced GC/GEJC from the perspective of the Chinese health service system.MethodsA three-state partition survival model was constructed to evaluate the economics of tislelizumab combined with chemotherapy as the first-line treatment of advanced GC/GEJC. Clinical data were collected from the RATIONALE-305 trial, and the incremental cost-effectiveness ratio (ICER) was calculated using quality-adjusted life years (QALYs) as the output index. The stability of the results was verified using sensitivity and subgroup analyses. In addition, scenario analysis was conducted for the model simulation time and different parameter extrapolation models.ResultsThe results of basic analysis showed an increase of 0.31 QALYs in the tislelizumab group compared with the placebo group (1.53 QALYs vs 1.22 QALYs), and a concomitant increase in cost of 10,326.68 USD, with an ICER of 33,876.38 USD/QALY, which is less than the current Chinese willingness-to-pay threshold (36,924.80 USD/QALY). Sensitivity analyses demonstrated that the utility values of progression-free survival, progressive disease and the price of capecitabine had a greater impact on the model. Subgroup analysis revealed that combination therapy was equally cost-effective in people with a program death ligand 1 tumor area positivity score of ≥5%.ConclusionFrom the perspective of the Chinese health service system, the treatment of advanced GC/GEJC with tislelizumab combined with chemotherapy has a cost-effective advantage over chemotherapy alone.